Writers for children critical studies of major authors since the seventeenth century - Bingham, Jane (New York Charles Scribner's Sons, 1988)
Critical studies of major children's authors since the seventeenth century. Entries include biographical information, critical analysis, and bibliographies of key primary and secondary works.
Louisa May Alcott -- Hans Christian Andersen -- Edward Ardizzone Asbjornsen and Moe -- J.M. Barrie -- L. Frank Baum -- Hilaire Belloc -- Ludwig Bemelmans -- Margery Williams Bianco -- William Blake -- Arna Bontemps -- Carol Ryrie Brink -- Jean De Brunhoff -- John Bunyan -- Frances Hodgson Burnett -- Virginia Lee Burton -- Lewis Carroll -- C. Collodi -- Padraic Colum -- James Fenimore Cooper -- James Henry Daugherty -- Daniel Defoe -- Walter de la Mare -- Charles Dickens -- Mary Mapes Dodge -- Sir Arthur Conan Doyle -- Alexandre Dumas -- Elizabeth Enright -- Juliana Horatia Ewing -- Eleanor Farjeon -- Rachel Lyman Field -- Wanda Gag -- Kenneth Grahame -- Jacob and Wilhelm Grimm -- Lucretia P. Hale -- Joel Chandler Harris -- Nathaniel Hawthorne -- E.T.A. Hoffmann -- Heinrich Hoffmann -- Langston Hughes -- Washington Irving -- Joseph Jacobs -- Erich Kastner -- Charles Kingsley -- Rudyard Kipling -- Andrew Lang -- Robert Lawson -- Edward Lear -- C.S. Lewis -- Hugh Lofting -- George Macdonald -- Frederick Marryat -- Cornelia Meigs -- A.A. Milne -- M.L.S. Molesworth -- L.M. Montgomery -- E. Nesbit -- Charles Perrault -- Beatrix Potfer -- Howard Pyle -- Arthur Ransome -- Marjorie Kinnan Rawlings -- Laura E. Richards -- Elizabeth Madox Roberts -- Christina Rossetti -- John Ruskin -- Felix Salten -- Carl Sandburg -- Ruth Sawyer -- Kate Seredy -- Anna Sewell -- Johanna Spyri -- Robert Louis Stevenson -- Frank R. Stockton -- Jonathan Swift -- J.R.R. Tolkien -- Mark Twain -- Hendrik Willem Van Loon -- Jules Verne -- H.G. Wells -- Kate Douglas Wiggin -- Oscar Wilde -- Laura Ingalls Wilder -- Charlotte Mary Yonge.
Keywords: Children's literature -- History and criticism